2013
DOI: 10.1074/jbc.m112.442814
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling to Characterize Disease-related Bacteria

Abstract: Background: Phenotypic profiling of knockout libraries is a possible functional genomics strategy.Results: Gluconate excretion is a novel phenotype of the Pseudomonas aeruginosa rpoN mutant, which is also weakly associated with antibiotic susceptibility in a clinical strain panel.Conclusion: The rpoN phenotype results from catabolite repression deregulation of 6-phosphogluconate dehydratase.Significance: NMR profiling can uncover novel gene functions with potential clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…This observation is consistent with a previous finding that the number of P. aeruginosa persister cells increases in response to QS and virulence factors (6). Additionally, it has been reported that the loss of rpoN through the deregulation of glucose metabolism increases gluconate production, which correlates with reduced susceptibility to several antibiotics (56).…”
Section: Discussionsupporting
confidence: 82%
“…This observation is consistent with a previous finding that the number of P. aeruginosa persister cells increases in response to QS and virulence factors (6). Additionally, it has been reported that the loss of rpoN through the deregulation of glucose metabolism increases gluconate production, which correlates with reduced susceptibility to several antibiotics (56).…”
Section: Discussionsupporting
confidence: 82%
“…This adaptation has been termed “metabolic adaptation” [24, 25]. The metabolic changes provide a mechanism to diminish oxidant production and to enhance the production of NADPH, which promotes the formation of antioxidants, as opposed to NADH, which is prooxidant.…”
Section: Biofilms and Oxidant Stressmentioning
confidence: 99%
“…The detected resonances in NMR spectra were assigned by means of the well established NMR Suite Professional version 7.1 (Chenomx, Alberta, Canada)2627, 2D homonuclear NMR experiments and most reliable online NMR databases based on experimentally acquired spectra: the online Human Metabolome Database28 and Biological Magnetic Resonance Data Bank29 (see Methods for details).…”
Section: Resultsmentioning
confidence: 99%